The urban network of La Coruña and the dynamics of metropolitan development - Díaz Fernández, José Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Knowledge of the urban environment of La Coruña constitutes a basic theme for the study of the regional territorial reality of Galicia. Thus, the analysis of the city model, its historical evolution, its urban network and its territorial characteristics, facilitate the interpretation of the evolutionary conformation of the urban network. To do this, by studying through the management of the different historical cartographies of the city we will be able to have relevant information about its physical and territorial characteristics; its articulation in the Spanish urban system, etc.